Keragaan Kapilaritas Air di Tanah Gambut yang Diaplikasikan Membran SWRT pada Tutupan Lahan yang Berbeda - Muhammad Imam Nugraha (Jurnal Solum, 2023)
Plants, water, and peat soil interact to form peatland ecosystems, which are composed of these three interrelated elements. The water balance of peatlands is significantly influenced by the capillarity of the peat soil. This study attempts to ascertain the impact of depth on applying subsurface water retention technology (SWRT) membrane on capillary action based on moisture of peat soil in different land uses. A completely nested randomized design was utilized in this investigation to avoid bias of the different degree of decomposition between land uses. The type of land use—namely, shrubs (PL1) and agricultural land (PL2)—was the first account. The position of the membrane (its depth), which was set at -20 cm (D1), -30 cm (D2), and -50 cm (D3) and in addition to a control treatment without membrane installation (D0), was the second account. Three times each experimental unit was repeated. The YL-100 soil moisture content sensor, which is powered by Arduino, presented the research results. Arduino can produce digital values with a range of 0 to 1023 by converting moisture values that were output as analog signals into digital values using an analog to digital converter (ADC) with a resolution of 10 bits. The outcome revealed that soil moisture content increasing up to the peat soil layer of 5 to 10 cm until the fifth day of observation due to rainfall along our study that increased the flux of water flow into the peat soil.